MEMAHAMI KONSEP METODOLOGI AL-JARH WA TA’DIL - Budi Suhartawan (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2024)
The purpose of this article is to dismantle the concept of the al-jarh wa ta'dil methodology easily and as a test tool for assessing hadith narrators in terms of weaknesses (jarh) and also strengths (ta'dil). The research method in this journal is literature study. The studies found in understanding the concept of jarh wa' ta'dil. Among others; first, the urgency of the science of al-jarh wa al-ta'dil as an art in determining whether the category of a narrator's narration can be accepted or rejected. Second, the history of the science of Jahr wa al-ta'dil has grown since the time of the Companions. Third, the techniques and methods of ulama when explaining the behavior of narrators and the conditions of critics (al-jarh wa ta'dil) when evaluating narrators. Fourth, the conception and editorial of Jarh wa al-Ta'dil and its scope.